Democracy in the Age of Globalization and Mediatization - Kriesi, H. author. aut Link
XIII, 250 p.
Keywords: This book provides comprehensive coverage of the models of contemporary democracy; its social, cultural, economic and political prerequisites; its empirically existing varieties and its two major challenges - globalization and mediatization. The book also covers the global spread of democracy and its spread into supranational democracies.